Synporins--synthetic proteins that emulate the pore structure of biological ionic channels. - Montal, M (1990)
A class of proteins that mimic the fundamental pore structure of authentic ionic channels has been designed, synthesized, and characterized. The design is based on our earlier result that a 23-mer peptide with the sequence of the M2 segment of the Torpedo californica acetylcholine receptor delta subunit--Glu-Lys-Met-Ser-Thr-Ala-Ile-Ser-Val-Leu-Leu-Ala-Gln-Ala-Val-Phe -Leu- Leu-Leu-Thr-Ser-Gln-Arg--forms cation-selective channels in lipid bilayers, presumably by self-assembly of conductive oligomers. Accordingly, a tethered parallel tetramer was synthesized with four M2 delta peptides attached to a carrier template--a 9-amino acid backbone with four attachment sites. As expected, the complete 101-residue protein does form channels in lipid bilayers reproducing several features that are characteristic of authentic acetylcholine receptor channels, such as single-channel conductance, cation selectivity, transitions between closed and open states in the millisecond time range, and sensitivity to local anesthetic channel blockers. An analogue protein, in which the serine residue in position 8 is replaced with alanine in each of the four M2 delta 23-mer peptides ([Ala8]M2 delta), also forms channels that, however, exhibit lower single-channel conductance. By contrast, a similar tethered tetramer with M1 delta peptides does not form channels, in accord with expectations. The general validity of this strategy to other channel sequences and oligomer numbers is anticipated. Thus, synporins--a term coined to identify this class of synthetic pore proteins--enrich our armamentarium directed toward the elucidation of structure-function relationships.